Mechanobiology Assays with Applications in Cardiomyocyte Biology and Cardiotoxicity - Blair, Cheavar A. (Adv Healthc Mater, 2020)
The mechanical phenotype of cardiomyocytes is essential to their function as the motor unit of the heart. Traditionally, testing of drugs for cardiotoxic effects has relied on primary cardiomyocytes from animal models and focused on short-term, electrophysiological and arrhythmogenic effects. However, primary cardiomyocytes present challenges arising from their limited viability in culture, and tissue from animal models suffers from a mismatch in their physiology to that of human heart muscle. Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) can address these challenges. They also offer the potential to study not only electrophysiological effects but also changes in cardiomyocyte contractile and mechanical function in response to cardiotoxic drugs. With growing recognition of the long-term cardiotoxic effects of some drugs on subcellular structure and function, there is increasing interest in using hiPSC-CMs for in vitro cardiotoxicity studies. In this review, we provide a brief overview of techniques that can be used to quantify changes in the active force cardiomyocytes generate and variations in their inherent stiffness in response to cardiotoxic drugs. We conclude by discussing the application of these tools in understanding how cardiotoxic drugs directly impact the mechanobiology of cardiomyocytes and how cardiomyocytes sense and respond to mechanical load at the cellular level.